2020
DOI: 10.33438/ijdshs.716858
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 8 Weeks squat exercise program on body composition in young males

Abstract: Not only aerobic exercises, but also resistance exercises program with maximum effort for large muscle groups such as squat has also been reported to be effective on muscle and body fat mass. Thus, this study aims to investigate the effect of squat exercises program on body composition. The data of this study were collected from 18 young adult males in July 2019 after 8 weeks of training. Workouts were held in 3 days in a week with the 48 hours resting interval. Each session consists of 4 sets of 6 repetitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Heinrichet al have expressed that there is no significant alteration in body fat percentage values for both groups after 8 weeks high intensity functional strength training and medium level aerobic strength training implementations [59]. When literature has been examined, the studies conducted by Serin and Ziyagil, Neves et al and Doğan et al show parallelism with our study [43,53,58]. However, the studies by Tomljanović, et al and Heinrichet al have not been supporting [57,59].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Heinrichet al have expressed that there is no significant alteration in body fat percentage values for both groups after 8 weeks high intensity functional strength training and medium level aerobic strength training implementations [59]. When literature has been examined, the studies conducted by Serin and Ziyagil, Neves et al and Doğan et al show parallelism with our study [43,53,58]. However, the studies by Tomljanović, et al and Heinrichet al have not been supporting [57,59].…”
Section: Discussionsupporting
confidence: 55%
“…The decrease in traditional group has been explained with the high intensity of training. Serin and Ziyagil have expressed that there is a decrease in a significant level in body fat percentage values in men after 8 weeks squat exercise program [43]. Neves et al in their study conducting 8 weeks functional training implementations in Circuit format on female participants have seen that there is a decrease in body mass index and fat rates [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results of the study confirmed the opinion and experimental data of other authors [33][34][35] about the prevailing development of certain types of motor abilities according to their importance in the structure of special readiness of volleyball players (girls).…”
Section: Pedagogysupporting
confidence: 86%